EXPERIENCES AND SATISFACTION WITH NATIONAL HEALTH INSURANCE SCHEME AMONG NON-TEACHING STAFF OF COLLEGE OF MEDICINE, UNIVERSITY OF IBADAN, NIGERIA (2014)
National Health Insurance Scheme (NHIS) aims to ensure that every Nigerian has access to good health care services at affordable costs. Inspite of the NHIS benefits, poor utilisation rate has been documented in previous studies and out-of-pocket means of payment still remain high. This study was therefore designed to investigate the experiences, level of satisfaction and attitude towards NHIS among Non-Teaching Staff (NTS) of College of Medicine, University of Ibadan (CoMUI), Ibadan, Nigeria. This cross-sectional study involved 375 randomly selected consenting NTS of CoMUI from the 4 Faculties and 8 administrative Units. A semi-structured self-administered questionnaire was used to elicit information on the socio-demographic characteristics, experiences, satisfaction, attitude and factors influencing utilisation of NHIS. Experience, satisfaction and attitude were measured on 16-point, 18-point and 20-point scales respectively. Experience scores of <8 and ≥8 were rated bad and good respectively. Satisfaction scores of <9 and ≥9 were rated not satisfied and satisfied respectively. Attitude scores of <10 and ≥10 were rated negative and positive respectively. Nine Key Informant Interviews (KIIs) were conducted among heads of units and the most senior staff. Quantitative data were analysed using descriptive statistics, Chi-square and logistic regression tests at p≤ 0.05 while qualitative data were analysed thematically. Age of respondents was 42.9±8.0 years, 54.7% were males and 92.5% were married. Most (93.6%) of the respondents registered with NHIS, out of which 36.3% were not utilising NHIS services as at the time of conducting this study. Reported reasons for not using NHIS were non-availability of personal identification number (68.3%) and having a family clinic which they were reluctant to change (41.1%). Among users, 49.6% had good experience, 44.6% have benefitted from NHIS services, and 43.3% reported they were given prompt attention at the hospital. More than one third (38.9%) were satisfied with the type of services available from NHIS while 31.2% mentioned that NHIS services met all their health needs. Attitude score was 14.7±3.7, 47.2% had positive attitude towards NHIS while 21.1% carried their registration cards regularly. Attention given to the patients by the health workers (93.6%), having adequate information about the scheme (91.7%) and quick registration process (84.8%) were some of the factors perceived that could influence NHIS service utililsation. Young adults between 24-40years were more likely to have good experience compared to the middle age (OR: 0.35; 95% CI: 0.127–0.983). Majority of the key informants revealed that healthcare facilities were imposed on enrollees, registration process was very slow and no evidence of appraisal of service delivery. Most participants were not fully enlightened on the components and structure of NHIS. Some of the respondents had good experiences with National Health Insurance Scheme services, few of the workers were satisfied with the services received and less than half had positive attitude towards NHIS. Modification of existing policies guiding registration process and quality of service of National Health Insurance Scheme is advocated for. Frequent monitoring and evaluation of all the healthcare facilities for proper appraisal is hereby recommended.